Questions kids ask: index - Comely, Richard; Dickie, Alison (Grolier Toronto, 1989)
Questions Kids Ask: Index is a comprehensive reference guide that organizes and answers a wide variety of children's questions on topics ranging from science to daily life, fostering curiosity and learning.